Design, Realization, and Characterization of Advanced Adhesives for Joining Ultra‐Stable C/C Based Components. Issue 9 (20th July 2020) - Casalegno, Valentina; De la Pierre des Ambrois, Stefano; Corazzari, Ingrid; Turci, Francesco; Tatarko, Peter; Damiano, Olivier; Cornillon, Laurence; Terenzi, Andrea; Natali, Maurizio; Puglia, Deborah; Torre, Luigi; Ferraris, Monica
Abstract: The aim of this work is to develop high‐performance adhesives to join carbon fiber reinforced composites (C/C) for use in aerospace applications; in order to guarantee sound mechanical strength, a low coefficient of thermal expansion, and ease of application on large components. Several different adhesive formulations, based on phenolic or cyanate‐ester resins (charged with the maximum experimentally feasible amount of carbon‐based fillers), are developed and tested. The measurements of the lap shear strength at room temperature of the C/C joined by means of one phenolic and one cyanate ester‐based resin demonstrates that these formulations are the most suitable for the given application. A complete characterization, by means of viscosimetry, dilatometry, and thermal gravimetric analysis, coupled with gas analysis by means of mass spectroscopy, confirms that the phenolic‐based formulation is the most promising joining material. A nano‐indenter is used to obtain its Young modulus and hardness, both inside the joint and as a bulk cured adhesive. Abstract : The design of high performance adhesives for the joining of carbon fiber reinforced composites (C/C) is presented for ultra‐stable applications in the aerospace field. The performance of formulations based on phenolic and on cyanate‐ester resins (charged with carbon based fillers) is analyzed in terms of mechanical strength, low coefficient of thermal expansion, and ease of application on large components.